2020
DOI: 10.15616/bsl.2020.26.3.186
|View full text |Cite
|
Sign up to set email alerts
|

Mean Value of Median Nerve Cross-sectional Area in Healthy 20s and 30s in Busan Area

Abstract: This study was designed to investigate the median nerve cross-sectional area of the upper extremity which is the main cause of CTS in the 20s and 30s. The median nerve cross-sectional area (MNC-area) of each part of the upper limb was measured in healthy 20s and 30s females and males without neurological diseases or other diseases. This MNC-area was compared with the hand, wrist, finger, and other body indexes. The research group was divided into 20s female and male groups, and the 30s were also divided into f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…These findings suggest the differences in median nerve CSA for different ethnicities. 6 The impact of these factors has been mentioned in several studies, 15,16,[20][21][22][23][24] and some have been evaluated in the present study. Bae et al found that CSA is significantly correlated with gender, height, weight, and BMI.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…These findings suggest the differences in median nerve CSA for different ethnicities. 6 The impact of these factors has been mentioned in several studies, 15,16,[20][21][22][23][24] and some have been evaluated in the present study. Bae et al found that CSA is significantly correlated with gender, height, weight, and BMI.…”
Section: Discussionmentioning
confidence: 95%
“…Some studies emphasize that MNCSA is influenced by BMI. 21 On the other hand, Higginbotham et al found no significant correlation between CSA and BMI. 22 A meta-analysis by Shiri et al suggests that a square-shaped wrist predicts CTS in both men and women.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Regarding the relationships between physical characteristics and median nerve CSA, previous studies suggested a positive correlation between BMI and median nerve CSA [ 37 , 38 , 39 , 40 , 41 ]. Cartwright et al reported that mean age based on BMI was a major parameter for predicting median nerve CSA in healthy subjects [ 42 ].…”
Section: Discussionmentioning
confidence: 99%